2021
DOI: 10.1038/s41598-020-79441-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of dissolved O2 in bulk aqueous solutions and porous media using NMR relaxometry

Abstract: Effects of dissolved paramagnetic oxygen (O2) in water on 1H nuclear magnetic resonance (NMR) Carr-Purcell-Meiboom-Gill (CPMG) experiments is evaluated at a 1H Larmor frequency of 2 MHz. Dissolution of O2 into water significantly reduces the 1H transverse relaxation coefficient (T2). For deoxygenated water, T2 is 3388 ms, water at ambient atmospheric conditions (7.4 mg/L O2) exhibits a T2 of 2465 ms, and dissolution of 2710 mg/L O2 further reduces T2 to 36 ms. The results were fit with an empirical model to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To summarize, it is demonstrated that the presence of paramagnetic oxygen molecules has a crucial impact on ZULF NMR spectra and it should be taken into account in quantitative ULF relaxometry experiments. This finding also suggests the potential use of ZULF NMR relaxometry in the evaluation of paramagnetic gas impurities 41 , 42 .…”
Section: Resultsmentioning
confidence: 63%
“…To summarize, it is demonstrated that the presence of paramagnetic oxygen molecules has a crucial impact on ZULF NMR spectra and it should be taken into account in quantitative ULF relaxometry experiments. This finding also suggests the potential use of ZULF NMR relaxometry in the evaluation of paramagnetic gas impurities 41 , 42 .…”
Section: Resultsmentioning
confidence: 63%
“…Dissolved oxygen was not removed from water by nitrogen bubbling or other techniques, even if its presence leads to an increase of the relaxation rates. [31,32] Indeed, the influence of O 2 was considered as rather small when compared with other sources of errors in the measurement of relaxation rates as sample temperature fluctuations. The experiments were performed at three different pHs using different buffers: at pH 2 (KCl/HCl), at pH 3 (NaCl/Glycine/HCl), and at pH 4 (sodium acetate/acetic acid) or (sodium citrate/HCl).…”
Section: Samplementioning
confidence: 99%
“…From the catalysed H 2 O 2 decay stable paramagnetic O 2 is generated in a 1 : 2 ratio relative to the H 2 O 2 concentration (eqn ( 1) and ( 2)), resulting in PREs for nearby 1 H nuclei. 17 radical species produced in this process are extremely shortlived 16 and do not generate PREs within the experimental timeframe (Fig. 3).…”
mentioning
confidence: 91%